An Acyclic Arsenium Cation Stabilised by a Single P–As π‐Interaction and a Cyclic Diphosphinophosphonium Salt. (3rd July 2019) - Izod, Keith; Evans, Peter; Waddell, Paul G.
Abstract: Stable acyclic arsenium cations R2 As +, isoelectronic analogues of germylenes, are rare in comparison to the corresponding phosphenium cations. The first example of a diphosphaarsenium salt, [{(Dipp)2 P}2 As][Al{OC(CF3 )3 }4 ]⋅1 1 / 2  PhMe, is described. This salt exhibits remarkable stability due to the delocalisation of a lone pair from a planar phosphorus centre into the vacant p‐orbital at arsenic; the bonding in 2 has been probed by DFT calculations. An attempt to synthesise an analogous diphosphaphosphenium salt unexpectedly generated the cyclic phosphonium salt [ cyclo ‐{(Mes)P}2 P(Mes)2 ][BAr F 4 ]⋅CyMe through the cyclisation of a putative phosphine‐substituted diphosphene cation intermediate. Abstract : Das erste Diphosphaarsen‐Kation wurde synthetisiert. Dieses Kation ist aufgrund der Delokalisierung eines freien Elektronenpaares von einem planaren Phosphorzentrum in das vakante p‐Orbital des Arsenatoms erstaunlich stabil.